Stability analysis and numerical simulations of IVGTT glucose-insulin interaction models with two time delays - Saber, Sayed; Alalyani, Ahmad (Mathematical Modelling and Analysis, 2022)
This paper presents a systematic study of a mathematical model of glucose and insulin interaction with two time delays, with a focus on analytical studies, bifurcation analysis, and very well numerical simulations. This model based on the Intra-Venous Glucose Tolerance Test (IVGTT) and is presented with two time delays. One delay is the insulin response time to an increase in glucose concentration, and the hepatic glucose production time delay is the other. Then, we establish results on positivity, boundedness, and persistence. We also provide suﬃcient stability analysis conditions for both local and global asymptotic stability of the proposed models. For the latter, two diﬀerent strategies are used: stability bifurcation analysis and Lyapunov-Krasovskii functionals. We investigate diﬀerent regions of parameter space using two approaches, that yield diﬀerent sets of suﬃcient conditions for global stability. The bifurcation graphs generated from our extensive and carefully designed simulations complement and conﬁrm these analytical results. The insulin concentration level peaks after the glucose concentration level, according to the numerical simulations.